PENGARUH INTERNET MARKETING DAN EMOTIONAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Pengguna Parfum HMNS di Kota Jakarta) - Ahmad Fathoni; Saladin Ghalib; M. Hasanur Arifin; Rizky Muslim Hidayat (Business Administration, FISIP ULM, 2023)
This research aims to examine the influence of internet marketing and emotional marketing on purchase decisions among HMNS perfume users. The research approach used is quantitative method. The sampling technique employed is non-probability - accidental sampling, with a sample size of 110 respondents. Data collection was done using questionnaires, and data analysis was conducted using multiple linear regression. The results of the study indicate that internet marketing (X1) has a positive and significant impact on purchase decisions (Y), and emotional marketing (X2) also has a positive and significant impact on purchase decisions. Simultaneously, internet marketing and emotional marketing have a significant influence on purchase decisions.